Financial behavior of united territorial communities in the conditions of decentralization reform in Ukraine - Melnyk, Viktor; Shchur, Roman; Tsiupa, Oksana (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article deals with the study of amalgamated territorial communities functioning peculiarities during the decentralization in Ukraine. It contains substantiation of the territorial community’s financial behavior as a basis for efficient administrative and financial decisions, as well as a study of the character and model of this behavior. The research of the models and peculiarities of amalgamated territorial communities’ financial behavior allows assessment and forecast of their social and economic development vectors; establishing the grounds for subsidies and opportunities for the increase of financial solvency regarding the formation of their expenses and performance of functions and assignments, laid upon them. The results of the research have emphasized the need for further scientific studies of behavioral aspects of the amalgamated territorial communities’ financial resources forming, as well as substantiation of their financial decisions for the attraction of additional proceeds. Active implementation of decentralization reform in Ukraine has started only in 2014 with creation of amalgamated territorial communities. The authors have researched the essence of the amalgamated territorial community’s financial behavior, being the basis for the establishment of its financial solvency, sustainability, as well as social and economic development. The study found that the main factor influencing the financial behavior of amalgamated territorial communities in Ukraine in terms of the priority of their budget expenditures and investment activities is the size of the community (characterized by area and population). The authors also proved that the key motives for the financial behavior of amalgamated territorial communities in matters of priority of budget expenditures and investment activities are the following: increasing their own revenues and increasing the financial independence of local governments. This actualizes the search for their own ways to strengthen financial capacity and prepare attractive offers to investors and increase the number of jobs, as well as further unification of small local communities.